2013
DOI: 10.1021/jp312008m
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of the Solid State Properties of Al–Nb Mixed Oxides: A Photoelectrochemical Study

Abstract: Al−Nb containing mixed oxides were grown by anodizing sputter-deposited Al−Nb alloys of different compositions. A photoelectrochemical investigation was carried out in order to estimate the band gap, flat band potential, and conductivity type of these oxides as a function of their composition. The dependence of the band gap on the composition of mixed sp−d metal oxides has been rationalized by using a semiempirical correlation between the difference of electronegativity and band gap of oxides proposed in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 37 publications
9
46
0
Order By: Relevance
“…The determined bowing parameter is lower than the one reported for anodic Al-Nb mixed oxides, i.e., 4.3 eV. 4 Typically, a small value of the bowing parameter, and thus a small deviation from the linearity of the band gap of alloys, can indicate a good miscibility of the alloys, such as b ¼ 0.1, as estimated from polycrystalline CZGTS (Se) alloys. 20 A larger value of the bowing parameter, such as the one determined here and also reported for Al-Nb mixed oxides, indicates that the randomness in the alloys strongly influences the energy gap of the alloys.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…The determined bowing parameter is lower than the one reported for anodic Al-Nb mixed oxides, i.e., 4.3 eV. 4 Typically, a small value of the bowing parameter, and thus a small deviation from the linearity of the band gap of alloys, can indicate a good miscibility of the alloys, such as b ¼ 0.1, as estimated from polycrystalline CZGTS (Se) alloys. 20 A larger value of the bowing parameter, such as the one determined here and also reported for Al-Nb mixed oxides, indicates that the randomness in the alloys strongly influences the energy gap of the alloys.…”
mentioning
confidence: 69%
“…Several studies were dedicated to understanding the electronic properties and changes in the band gap of amorphous anodic Al 2 O 3 upon alloying. [3][4][5] Theoretical studies based on density functional theory have shown that transition metal atoms, such as Zr atoms present in Al sites, introduce localized d-electron states below the conduction band (CB) of Al 2 O 3 . 6 Experimental determination of the band gap energy of Zr-alloyed Al 2 O 3 is not readily available because ultraviolet and visible measurements are limited to energies below 6 eV due to the absorption of air.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure allowed correlation of the bandgap values measured by PCS with the mixed oxide composition, as confirmed with several mixed oxides of known composition. [3][4][5][6]8,9 In this work, we will discuss the limits of validity of Eqs. 1a and 1b for binary and ternary oxides spanning a large range of bandgap values (from ∼1 eV to ∼9 eV) by discussing data reported in the literature pertaining to ternary mixed oxides prepared by different techniques and including anodic passive films grown on metallic alloys.…”
mentioning
confidence: 99%
“…Semi-empirical correlation between the electronegativity and band gap of oxides has been used recently to estimate the band gap of mixed metal oxides. 4,5 While anodic Al oxide layers are widely used, few studies on band gap structure of anodic oxide films have been reported. 5 In this Letter, we study the effect of Ti alloying on the electronic structure and band gap states of amorphous anodic aluminum oxide.…”
mentioning
confidence: 99%